Pendidikan Karakter di Era Digital: Mengajarkan Etika dan Tanggung Jawab dalam Penggunaan Sosial Media - Tantri, Kikan Sandiyus; Aqilla, Nofi Arum; Sukmawati, Anis (Lembaga Yasin AlSys, 2023)
Character education is a proactive effort to support a person's capacity to understand, pay attention to, and uphold basic ethical principles. The use of social media by children, adults and parents is increasing in this digital era as technology becomes more complex. Children can easily use digital media in this digital era. In addition, there are positive and negative impacts of using social media. As a result of recent changes, many students now utilize technology for pleasure and have poor morals and social attitudes.In today's digital era, teaching children how to utilize technology ethically is essential to developing their moral character. Therefore, character education is necessary to create a good generation by instilling a sense of responsibility in the utilization of modern technology in the digital era. So this article will discuss character education in the digital era and how to use social media ethically.